2015
DOI: 10.1021/acs.jafc.5b02649
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin Modifies the Composition of Fecal Microbiota and Increases Cecal Levels of Short-Chain Fatty Acids in Rats

Abstract: There has been particular interest in the prebiotic-like effects of commonly consumed polyphenols. This study aimed to evaluate the effects of hesperidin (HD) and its aglycone hesperetin (HT), major flavonoids in citrus fruits, on the structure and activity of gut microbiota in rats. Rats ingested an assigned diet (a control diet, a 0.5% HT diet, or a 1.0% HD diet) for 3 weeks. Terminal restriction fragment length polymorphism analysis revealed that the proportion of Clostridium subcluster XIVa in the feces co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…After centrifugation, the supernatant was passed through disposable solid‐phase extraction column cartridges (Strata‐X, 30 mg/ml, Phenomenex, Inc., Torrance, CA, USA), and 0.4 ml of the passed eluate was added to the same volume of acetonitrile. After centrifugation at 5,000 g for 10 min, liberated maltose in the supernatant was measured by the HPLC system (Unno et al., ). The rate of enzyme inhibition (%) was calculated as maltose concentration in the resulting mixture relative to the control (without GTE or BTE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After centrifugation, the supernatant was passed through disposable solid‐phase extraction column cartridges (Strata‐X, 30 mg/ml, Phenomenex, Inc., Torrance, CA, USA), and 0.4 ml of the passed eluate was added to the same volume of acetonitrile. After centrifugation at 5,000 g for 10 min, liberated maltose in the supernatant was measured by the HPLC system (Unno et al., ). The rate of enzyme inhibition (%) was calculated as maltose concentration in the resulting mixture relative to the control (without GTE or BTE).…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation at 5,000 g for 10 min, liberated maltose in the supernatant was measured by the HPLC system (Unno et al, 2015). The rate of enzyme inhibition (%) was calculated as maltose concentration in the resulting mixture relative to the control (without GTE or BTE).…”
Section: Inhibition Of Pancreatic α-Amylase In Vitromentioning
confidence: 99%
“…Dietary supplements, or nutraceuticals, have been used extensively as a natural treatment for CVD and related diseases as they exhibit antioxidant, anti‐inflammatory, or hypotensive effects . In particular, hesperidin, a flavanone glycoside that is found abundantly in citrus fruits, is metabolized by the gut microbiota to its aglycone form, hesperetin , which is known to have cardioprotective effects , and some studies already demonstrated its hypotensive effects in spontaneously hypertensive rats (SHR) . Roowi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria associated with fermented foods may influence gut-associated microbial composition and function by direct competition, by metabolic interaction, through direct immune activation, or via the production of bioactive molecules, such as the short-chain fatty acids (SCFAs), that are able to influence the host health regulating a number of immune and non-immune protective mechanisms (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%